THE SINGLE-PARTY ERA LAW ENACTED AND PREPARED TO TAKE CONTROL OF THEIR FAMILY LINE REPORTS - Ahmet İLYAS (Fırat University, 2019)
In this study, the One-Party Administration has done is to take control of tribal laws and prepared reports, is located. The main theme of the study, the Kemalist rule, Eastern and Southeastern Anatolia Region, to build a nation-state structure is based on the work they are doing. In particular, the Sheikh Said Rebellion, the central government quashed memorization. In this case, the formation of the Balkan Syndrome or alleged to be erased from the memory can. Indeed, from the Balkans after the Balkan Wars homeland for centuries, hundreds of thousands of citizens of the Ottoman State, has been to Istanbul. This situation has created the trauma and fear of